RANCANG BANGUN APLIKASI SI-WAJA BERBASIS ANDROID UNTUK MENCEGAH KECELAKAAN LALU LINTAS DI KOTA SURAKARTA - Masrukin, Masrukin; Budiharjo, Anton; Budi P, Agus; Maulyda, Mohammad Archi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2020)
The needs of land transportation grows rapidly each year, along with the increasing population and mobility. It threatens the safety of road users if not handled appropriately. From 2015 to 2018 accidents in the city of Surakarta were relatively increased by the number of accidents in 2018 was 834 events. 55% of accident events caused by road users are not orderly. There is already handling done, but not effective. No one has overcome the blackspot with technology. Si Waja application is designed to reduce traffic accidents. Si Waja application serves to improve the driver's attention. The process of designing this application using methods of research and development. Application design Si Waja uses Android Studio integrated with Firebase. There are two tests conducted to test the Si Waja application Black Box Testing and Usability Testing. All elements in the application go well, evidenced by the Black Box Testing. This usability test uses the System Usability Testing (SUS) method which provides adequate results based on the consideration of small sample quantities, time, and cost. The SUS calculation result will be converted to certain values. This conversion result will give the app information that is made worthy or unfeasible to implement. From the 100 total value, Si Waja obtained 71,833, with index B. It means that this application is eligible to be applied in Surakarta.